Analisis Semiotika Tanda Otaku Idol dalam Anime Back Street Girls: Gokudols - Hariananta, Leonika; Ni Nengah Suartini; Gede Satya Hermawan (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This study aims to describe semiotic signs of otaku idol on Back Street Girls: Gokudols anime. Using descriptive qualitative method with Roland Barthes’ (1972) two order of signification semiotic analysis produced the denotative, connotative and myth of signs. The result of the study showed there are visual and verbal data that indicate signs of otaku idol. The denotation meaning could be understood from characterization of otaku, visual scenes and verbal dialogues. The connotation meaning showing the concepts of otaku appearance, consumerism pattern, obsession, delusion, imitation and sexual connotation. While the myth reference to otaku character design, consumerism ideology, celebrity worship phenomenon, and sexual deviance.